H-bonding networks of the distal residues and water molecules in the active site of Thermobifida fusca hemoglobin - Nicoletti, Francesco P. (2013)
The ferric form of truncated hemoglobin II from Thermobifida fusca (Tf-trHb) and its triple mutant WG8F-YB10F-YCD1F at neutral and alkaline pH, and in the presence of CN− have been characterized by resonance Raman spectroscopy, electron paramagnetic resonance spectroscopy, and molecular dynamics simulations. Tf-trHb contains three polar residues in the distal site, namely TrpG8, TyrCD1 and TyrB10. Whereas TrpG8 can act as a potential hydrogen-bond donor, the tyrosines can act as donors or acceptors. Ligand binding in heme-containing proteins is determined by a number of factors, including the nature and conformation of the distal residues and their capability to stabilize the heme-bound ligand via hydrogen-bonding and electrostatic interactions. Since both the RR Fe-OH− and Fe-CN− frequencies are very sensitive to the distal environment, detailed information on structural variations has been obtained. The hydroxyl ligand binds only the WT protein giving rise to two different conformers. In form 1 the anion is stabilized by H-bonds with TrpG8, TyrCD1 and a water molecule, in turn H-bonded to TyrB10. In form 2, H-bonding with TyrCD1 is mediated by a water molecule. Unlike the OH− ligand, CN− binds both WT and the triple mutant giving rise to two forms with similar spectroscopic characteristics. The overall results clearly indicate that H-bonding interactions both with distal residues and water molecules are important structural determinants in the active site of Tf-trHb.